Control of the convective flow instabilities in a simulated Czochralski growth system - SOLTANI, N.; S. RAHAL (International Scientific Journal FDMP: "Fluid Dynamics and Materials Processing", 2017)
A three-dimensional time-dependent numerical study of the flow instabilities in a simulated Czochralski system is conducted. The comparison with previously published experimental results is reported. The simulations were performed using a refined grid in order to investigate flow instabilities in the crucible. Simulations have been carried out for various crystal rotational speeds, by taking into account the effects of Rayleigh and Marangoni numbers. The temperature fluctuations near the crystal/liquid interface are analyzed. The method used for that purpose is the Fast Fourier Transform with the corresponding spectra. From numerical simulations, it has been observed that for rotational speeds of the crystal less than 10 rpm, the temperature fluctuations are increased until a magnitude of 1.1 K over a period of 6 min. For crystal speeds larger than 10 rpm the fluctuations are extremely reduced to a magnitude less than 0.02 K.